The effect of white‐tailed deer density on breeding songbirds in Delaware - Elizabeth L. Tymkiw; Jacob L. Bowman; W. Gregory Shriver (Wildlife Society Bulletin)
ABSTRACT Most population goals for white‐tailed deer (Odocoileus virginianus) are based solely on deer data, with little consideration for other parts of the ecosystem. A wider ecological approach is needed for more justifiable target deer densities. We investigated the use of birds as coarse‐scale indicators to determine an ecological carrying capacity for deer management by studying the relationship between the forest bird community and deer density in Delaware, USA. Using Breeding Bird Survey data from 2005 to 2009, targeted point‐count data from 2008 to 2009 and Division of Fish and Wildlife deer‐density data from the same time periods, we compared avian species richness and relative abundance with deer density. We divided deer densities into low (≤10 deer/km2), moderate (11–19 deer/km2), and high (≥20 deer/km2) categories. We placed birds into 6 deer‐sensitive guilds: interior forest obligates, ground nesters, shrub nesters, ground gleaners, low‐canopy foragers, and Neotropical migrants, as well as 1 “guild” that consisted of species found to be sensitive to deer density in past literature. The abundance or richness of most guilds and species did not differ by deer density. However, there were 1.08 more shrub nesters and 0.55 more species of shrub nesting birds in low‐deer‐density areas than in high‐deer‐density areas. Areas of moderate and low deer densities had ≥0.35 more species of low‐canopy foragers than did areas of high deer densities. Low‐deer‐density areas had ≥0.59 more individual Neotropical migrants compared with moderate‐ or high‐deer‐density areas. Similarly, areas of low deer densities had ≥0.49 more migrant species than did areas of higher densities. Low‐deer‐density areas had ≥0.17 more ovenbirds compared with high‐ and moderate‐deer‐density areas. Great crested flycatchers (Myiarchus crinitus) had 3 times greater odds of being found in low‐deer‐density areas than in high‐deer‐density areas. Chipping sparrows (Spizella passerina), Acadian flycatchers (Empidonax virescens), and red‐eyed vireos (Vireo olivaceus) all had 2 times greater odds of being found in low‐deer‐density areas than high‐deer‐density areas. Our results suggest that areas in Delaware with densities of <20 deer/km2 have the greatest avian richness and abundance. These findings are the first step toward determining an ecological carrying capacity for white‐tailed deer. © 2013 The Wildlife Society.